2005
DOI: 10.1128/aac.49.10.4339-4343.2005
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin Gallate Inhibits Biofilm Formation by Ocular Staphylococcal Isolates

Abstract: Epigallocatechin gallate (EGCg), the main polyphenol component of green tea, has several antibacterial properties. Here we show that sub-MICs of EGCg appear to decrease slime production, therefore inhibiting biofilm formation by ocular staphylococcal isolates previously characterized for the presence of ica genes by the Congo red agar plate assay and for adhesion to microtiter plates.Biofilm formation is a three-stage process (6) that significantly contributes to the pathogenesis of staphylococcal infections. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(84 citation statements)
references
References 21 publications
4
78
0
2
Order By: Relevance
“…The properties of green tea which inhibit bacterial growth are mainly related to their polyphenolic components including epicatechin, epicatechin gallate, epigallocatechin, and epigallocatechin gallate against various Gram-positive and Gram-negative bacteria [22,23] . Green tea was also reported to have a synergistic effect with β-lactam antibiotics against MRSA [24][25][26][27][28] , It was also reported that the main component of tea polyphenols, epigallocatechin gallate can reverse methicillin resistance of MRSA by inhibiting the synthesis of PBP2 [29] , Epigallocatechin gallate not only increases the activity of β-lactams but also increases the activity of non-β-lactam cell wall biosynthesis inhibitors [26] .…”
Section: Discussionmentioning
confidence: 99%
“…The properties of green tea which inhibit bacterial growth are mainly related to their polyphenolic components including epicatechin, epicatechin gallate, epigallocatechin, and epigallocatechin gallate against various Gram-positive and Gram-negative bacteria [22,23] . Green tea was also reported to have a synergistic effect with β-lactam antibiotics against MRSA [24][25][26][27][28] , It was also reported that the main component of tea polyphenols, epigallocatechin gallate can reverse methicillin resistance of MRSA by inhibiting the synthesis of PBP2 [29] , Epigallocatechin gallate not only increases the activity of β-lactams but also increases the activity of non-β-lactam cell wall biosynthesis inhibitors [26] .…”
Section: Discussionmentioning
confidence: 99%
“…Then plates were inoculated and incubated aerobically for 24 to 48 h at 37°C. Presence of black colonies with a dry crystalline revealed that bacteria are biofilm producing and non-producers remain pink (Freeman et al, 1989 andBlanco et al, 2005) Microtiter plate (MtP) assay The test was performed according to Christensen et al (1982). The Overnight bacterial cultures were diluted 1:10 with Trypticase Soy Broth, 96-well microtiter plates were used and seeded with 200 µL per well.…”
Section: Assay Of Biofilm Productionmentioning
confidence: 99%
“…Previous studies have reported that green tea polyphenols (TPP), collectively termed catechins including epicatechin (EC), epicatechin gallate (ECG), epigallocatechin (EGC), and epigallocatechin gallate (EGCG), have bactericidal activity against various Gram-positive and Gram-negative bacteria [3,13,23]. Recently, EGCG was reported to act synergistically with various b-lactam antibiotics against MRSA [10-12, 21, 22].…”
Section: Introductionmentioning
confidence: 99%